A preliminary study on thermal ablation of lung tumors - Carlo Ambrogi, Marcello; Fontanini, Gabriella; Lencioni, Riccardo; Fanucchi, Olivia; Crocetti, Laura; Faviana, Pinuccia; Franchini, Chiara; Mussi, Alfredo; Alberto Angeletti, Carlo (Contemporary Oncology/Współczesna Onkologia, 2004)
Introduction. Recently, percutaneous thermal ablation of focal malignancy has received much attention due to its promising results in the treatment of primary and secondary neoplasms. Its feasibility, toxicity and efficacy on lung tumors have been evaluated through a research program, started in January 2001, whose first three preliminary phases and their results are reported herein. Methods. Radiofrequency thermal ablation (RFA) was initially performed on lung tissue in an animal model (rabbit) and on lung tumors in two human models. A 150 W automatic generator (Model 1500, RITA Medical System, Mountain View, CA) and multiple electrode device (StarBrust XL, RITA Medical System, Mountain View, CA) were utilized for all the phases. It consists of a 15-gauge needle with nine deployable electrodes which open laterally in the flower-like manner up to 5 cm. The percutaneous approach was utilized in the animal model, under fluoroscopic guidance. In the human models, instead, radiofrequency ablation of a lung tumor was performed on the bench just after surgical resection in the first model, and via open thoracotomy just before surgical resection in the second model. The target temperature was 90°C in all the cases. It was maintained for 4 minutes in the animal model (with electrodes deployed 1 cm) and 20 minutes in the human models (with electrodes deployed 5 cm). Animals were euthanized at programmed intervals (day 0, 1, 3, 15, 30) and their specimens, as well as those of the human models, underwent pathological study. Results. Radiological and pathological examinations on 15 rabbits assessed the efficacy in producing a limited lesion without significant toxicity and permanent damage to peripheral parenchyma. In the human models, pathological study assessed complete ablation of the tumor on 7 out of 10 treated cases. Instead, in 3 cases the residual clusters of neoplastic cells were seriously damaged. Conclusions. RFA seems to be safe and efficacious in the treatment of lung tumors. An array with deployable electrodes seems to be preferable to avoid multiple insertion. Now, clinical trials of percutaneous CT-guided RFA are required to confirm these preliminary results and to define which patients qualify for this treatment.